The concepts of "I" and "We" and their relationship with the concept of "personality in history" in the epic novel "War and Peace" - A.K. Rashidov, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
It is in this law, in my opinion, that the meaning of the concept of personality in history lies, brightly and colorfully reflected in Tolstoy's epic novel War and Peace.